(21b-6)-5(4b+1)=-4

Simple and best practice solution for (21b-6)-5(4b+1)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (21b-6)-5(4b+1)=-4 equation:


Simplifying
(21b + -6) + -5(4b + 1) = -4

Reorder the terms:
(-6 + 21b) + -5(4b + 1) = -4

Remove parenthesis around (-6 + 21b)
-6 + 21b + -5(4b + 1) = -4

Reorder the terms:
-6 + 21b + -5(1 + 4b) = -4
-6 + 21b + (1 * -5 + 4b * -5) = -4
-6 + 21b + (-5 + -20b) = -4

Reorder the terms:
-6 + -5 + 21b + -20b = -4

Combine like terms: -6 + -5 = -11
-11 + 21b + -20b = -4

Combine like terms: 21b + -20b = 1b
-11 + 1b = -4

Solving
-11 + 1b = -4

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 1b = -4 + 11

Combine like terms: -11 + 11 = 0
0 + 1b = -4 + 11
1b = -4 + 11

Combine like terms: -4 + 11 = 7
1b = 7

Divide each side by '1'.
b = 7

Simplifying
b = 7

See similar equations:

| x*.54=210 | | K/7=2 | | x*.54=250 | | 2/3x-7/3=6 | | x*.7=250 | | 7x(4+3-5)= | | x*.16=40 | | 9x+9=45+x | | 5(x-4)=2x+5(x-2) | | x*.44=110 | | 8x=90+2x | | 16(3x)=64(x+5) | | h(x)=(2x-6) | | 28-0.3=0.74-12 | | 9(w-6)= | | 8w^2-2122w+20000=0 | | 2d+4=10+6d | | 11-7*2+3= | | x*.16=4 | | (x^3)+(5x^2)-x-5=0 | | 8/7y-4/7 | | 8x+10=6x-12 | | x*.15=3 | | 4c=2c+9 | | 7.37x+64=54.3169+8x | | 6/7x-3/7=9 | | 6.95x+34.75=69.5 | | 99-w=208 | | 8.6a+11=114.2 | | 21=8d-9(2d+1) | | x^2+14x-106=0 | | 10/11x-2/11=5 |

Equations solver categories